2020
DOI: 10.1016/j.jclepro.2019.118436
|View full text |Cite
|
Sign up to set email alerts
|

The link between particle size and froth stability - Implications for reprocessing of flotation tailings

Abstract: Historic tailings dams can often be considered as valuable mineral reserves due to the declining head grades of primary deposits. The reprocessing of such material is of great interest to the minerals processing industry, not only from an economic point of view, but also from an environmental one. However, tailings material is generally comprised of fine particles, which poses a challenge for its reprocessing using froth flotation due to reduced recoveries of these particle sizes. In addition, there is some de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The agreement obtained with different experimental procedures and equipment supports the hypothesis that pulp bubble size affects froth stability. It also supports the observation that there is a good agreement between the dynamic froth stability and the air recovery, as shown by Mackay et al (2020).…”
Section: Relationship Between Bubble Size and Froth Stabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…The agreement obtained with different experimental procedures and equipment supports the hypothesis that pulp bubble size affects froth stability. It also supports the observation that there is a good agreement between the dynamic froth stability and the air recovery, as shown by Mackay et al (2020).…”
Section: Relationship Between Bubble Size and Froth Stabilitysupporting
confidence: 88%
“…Froth stability can be affected by many factors, such as particle size and hydrophobicity (Ata, 2012;Norori-McCormac et al, 2017;Mackay et al, 2018Mackay et al, , 2020, frother type and concentration (Harvey et al, 2005;Wiese et al, 2011;McFadzean et al, 2016;Mesa et al, 2016), froth depth (Hadler et al, 2012) and impeller speed , among others. In particular, impeller speed generates turbulence within the pulp that can affect the pulp-froth interface (Schubert, 1999;Brito-Parada et al, 2017).…”
Section: Froth Stabilitymentioning
confidence: 99%
“…The optimum superficial air velocity for each pilot test was not evaluated in this work. Mackay et al [4] highlighted the importance of considering the connection between particle size, air rate and froth stability when determining flotation strategies. Thus, the implementation of automatic air flow control in the cavitation system can also contribute to improve the results obtained in a slime flotation industrial circuit since, in addition to the variability of the run of mine, some adjustments in the industrial plant may change the size distribution of the slimes flotation feed, requiring a new optimized air flow, since these changes in the particle size distribution require a change in the air rate to maximize mineral recovery [5].…”
Section: Carrying Ratesmentioning
confidence: 99%
“…Achaye [3] showed that froth stability decreases with increasing particle size and fine particles had the greatest influence on froth stability. Some authors [4,5] investigated the relationship between froth stability, size distribution, and air recovery, demonstrating there is an ideal air rate for each particle size distribution.…”
Section: Introduction 1iron Ore Ultrafines Concentrationmentioning
confidence: 99%
“…As tailings have already been floated once, re-flotation in some cases is possible [10], but can result in low recoveries because of non-floatable minerals or very fine grain sizes. The small grain size can at least in part be overcome by using a tailored size distribution of the tailings material [11]. Besides froth flotation, leaching is the second most common method to process copper ore. Leaching can be carried out via conventional sulfuric acid leach or with support of bacteria.…”
Section: Introductionmentioning
confidence: 99%